Texture-Modified Diets and Practical Swallowing Interventions in Head and Neck Cancer Patients with Dysphagia: A Narrative Review - Chyntia Glori Tania; Nasri Nasri (Majalah Kesehatan Indonesia, 2026)
Dysphagia is one of the most prevalent and persistent complications in patients with head and neck cancer (HNC), particularly nasopharyngeal carcinoma (NPC), with a reported prevalence of 45–83%. This narrative review aimed to synthesize recent evidence (2015–2025) on the effectiveness of texture-modified diets and swallowing therapies in improving nutritional intake, swallowing safety, and quality of life in HNC patients. Literature searches were performed systematically through PubMed, Scopus, Web of Science, Google Scholar, and Dimensions using predefined inclusion and exclusion criteria, resulting in 12 eligible articles for analysis. The findings showed that dysphagia significantly contributes to malnutrition, aspiration risk, prolonged hospitalization, reduced treatment adherence, and decreased survival. Interventions such as diets guided by the International Dysphagia Diet Standardisation Initiative (IDDSI), personalized nutritional strategies, and structured swallowing therapies demonstrated beneficial outcomes in reducing aspiration, maintaining oral intake, and improving clinical prognosis. In addition to synthesizing clinical outcomes, this review provides a theoretical contribution by framing dysphagia management as a multidisciplinary process that integrates nutritional science, swallowing physiology, and rehabilitative practice. Preventive swallowing exercises during radiotherapy and multidisciplinary management further enhanced long-term outcomes. The synthesis highlights the necessity of integrating nutrition and swallowing rehabilitation into routine oncology practice, with particular implications for healthcare facilities with limited resources where IDDSI adoption and preventive therapy remain underutilized. Future studies should prioritize high-quality randomized controlled trials, particularly in NPC populations, to validate intervention protocols and standardize best practices. This review contributes to bridging evidence with clinical application, providing a framework for safer and more effective patient-centered care.